Analisis Mutu Pelayanan Kesehatan Dalam Meningkatkan Pemanfaatan Pelayanan Kesehatan (Health Care Utilization) di Puskesmas Jaddih, Kabupaten Bangkalan - Rohilatul Jannah; Eka Suci Daniyanti; Soliha Soliha (Universitas Airlangga, 2025)
Background: Puskesmas (Primary Health Care) is the entry point or basic services accessible to all levels of society at the village level. However, the utilization of health services in Indonesia, including Madura, remains low. Objectives: To analyze community perceptions of the quality of health services and their influence on the utilization of health services at Puskesmas Jaddih, Bangkalan Regency, Madura. Methods: This was an explanatory research with a cross-sectional design. The population included all residents in the working area of Puskesmas Jaddih, with an average of 500 patient visits per month. A total of 149 patients who used health services at the Puskesmas Jaddih and met the inclusion criteria participated in the study. Data were analyzed using descriptive statistics and the Spearman test with a significance level of p<0.05. This study was conducted from January to December 2024. Results: Most patients had a primary education. More than half of the patients were not working. The majority rated the competence of health workers as very good. In terms of affordability, effectiveness, continuity, safety, convenience, and information, most rated it as excellent or good. In the SERVQUAL assessment, it was found that almost half of the total patients rated it as excellent (45.3%), just under half of the total patients rated it as good (44.1%), and a small proportion reported it as poor (10.6%). Most patients reported health care utilization in the order category (73.2%). A small proportion reported repeat orders (8.9%) and recommendations (17.9%). The results of statistical analysis showed that competence, affordability, effectiveness, continuity, safety, comfort, and information were related to health care utilization with p<0.05. Overall, in the SERVQUAL assessment, it was found that the results of SERVQUAL analysis with health care utilization showed p<0.05. Conclusion: The quality of health services at Puskesmas Jaddih is perceived by the community, effectiveness, and convenience. However, service utilization remains limited to initial use, with low levels of repeat visits and recommendations. All quality dimensions showed a significant relationship with healthcare utilization, indicating that community perceptions of service quality strongly influence decisions to use, re-use, and recommend health services.